The Influence of Influencer Marketing and Service Quality in Increasing Interest in Visiting Café Pesona Kampong - Sri Dela; Muammar Khaddapi; Muhammad Aqsa (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of influencer marketing and service quality on consumers' interest in visiting Café Pesona Kampong. The method used is a quantitative approach with survey techniques. The sample was determined using the Margin of Error (MoE) formula, so that 100 respondents were obtained. Data was collected through a Likert scale-based questionnaire that measured influencer marketing variables, service quality, and visitor interest. The results of the study show that influencer marketing has a positive and significant effect on visitor interest by forming a positive image of the café. The quality of service also has a significant influence, especially in creating loyalty and attracting consumers. Simultaneously, these two variables have a positive and significant influence on interest in visiting. The contribution of this research is to provide empirical evidence of the importance of digital marketing strategies and superior services in increasing consumer appeal. These findings can be the basis for the management of Café Pesona Kampong to continue to strengthen cooperation with relevant influencers and maintain consistency in service quality to increase competitiveness in the culinary industry.